(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Cerebral palsy (CP) is one of the main causes of limited activity in children. The prevalence of CP ranges from 2.6 to 2.9 per 1000 live births. Most of children with CP have at least one comorbid, including epilepsy. Epilepsy in CP is difficult to control, and can increase the severity of motor impairment and cognitive function, therefore the prognosis is poor. The incidence of epilepsy in CP is associated with a specific clinical profile. This study aimed to analyze the comparison of clinical characteristics of cerebral palsy in children with and without epilepsy. Methods: A cross-sectional study was conducted using medical record of children with cerebral palsy in pediatric neurology outpatient clinic in Dr. Soetomo Hospital Surabaya in March - May 2020. Children with CP who met the inclusion criteria were included in this study. The variables studied included sex, perinatal history (preterm birth, low birth weight, and neonatal asphyxia), neonatal seizures, spastic type, level of GMFCS, head circumference, neuroimaging features, hearing loss, and eye abnormalities. The study subjects were divided into two groups. Group 1 consisted of children with CP and epilepsy. Group 2 consisted of children with CP without epilepsy. Data analysis was performed using the Chi-square test and fisher’s exact test using SPSS. Result: Significant comparison of the characteristics were found in the history of neonatal seizures and the level of GMFCS. The percentage of neonatal seizures was higher in group 1 at 61.3% (p=0.049). The degree of GMFCS in group 1 was dominated by GMFCS III while in group 2 it was dominated by GMFCS IV (p=0.047). Subjects with GMFCS I and II levels were only found in group 2, while in group 1 with higher level of GMFCS, they were GMFCS III, IV, and V. More abnormal neuroimaging was found in group 1, namely 64.3%, while in group 2 it was 57.1%. There was no statistically significant difference of neuroimaging characteristics between the two groups (p= 0.911). Conclusion: There were differences in clinical characteristics associated with neonatal seizures and GMFCS between CP with and without epilepsy.